Factores que contribuyen y/o limitan la implementación del Plan de Salud Mental 2020-2021, en el centro de salud Bethania del distrito de El Agustino - Cruz Orozco, Marlon Renán (2024)
The current research sought to identify the factors that contributed to or limited the effective implementation of the MINSA Mental Health Plan 2020 – 2021, at the Bethania health center located in the district of El Agustino. Although health authorities have presented strategies that include actions with direct intervention in the community affected by the pandemic, an increase in mental problems has been seen in this part of the country. Specialists have detected the lack of selfcare and collective and supportive attention to mental health in homes within the health crisis caused by COVID-19. The research is qualitative, since it was intended to analyze the implementation of the Mental Health Plan 2020 - 2021 in the "Bethania" Health Center, through the collection of information from users (families of the Bethania Housing Association) and health personnel working at the aforementioned center. Likewise, an investigation was carried out through a detailed analysis of a particular situation, to the Mental Health Plan. With this fieldwork analysis, the effectiveness of the plan in the target population is detected. As part of the research process, an articulation is observed between the Bethania health center, the Bethania housing association, the jurisdictional police station, the municipality of El Agustino, among other institutions. It is important to note that despite the fact that more than 313 thousand people were treated for depression problems nationwide in 2021 alone, in vulnerable areas such as the Bethania housing association, the development of family resilience has been achieved in the context of COVID-19. In addition to stress management and the interest in promoting physical activity to help optimize the quality of life of the population. This detailed work tries to explain what have been the variables and/or factors that intervene in a correct execution of the mental health plan, after a global health crisis hit thousands of homes, directly affecting the mental health of millions of individuals. This is a new challenge that we hope will be used to banish the old model of health services specialized in mental health.